The Relationship Between the Effectiveness of Learning Physical Education Sports and Health on the Physical Fitness of 10-12 Year Old Students - Faisol Hamid; Kahan Tony Hendrawan (PHEDHERAL, 2023)
This study aims to determine the relationship between the Relationship Between the Effectiveness of Learning Physical Education Sports and Health Towards Physical Fitness of Students Aged 10-12 Years, this study is a correlational study that uses survey methods. The results of the study for learning effectiveness showed a sufficient category of 32 students (41.02%), for physical fitness 32 students (41.02%) in the moderate category, for the correlation test showed the sig value between physical fitness and the effectiveness of PJOK learning was 0.045 <0.05 which means there is a significant correlation or relationship between variables. The conclusion based on the results of the relationship between the effectiveness of PJOK learning and the physical fitness of students aged 10-12 years, so it needs to be understood when learning is effective and students do movement activities will have a positive impact on students' physical fitness.